The effect of perceived cultural adoption on dehumanization of refugees in honor culture - Yakın, Sevgi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Refugees are often dehumanized by host societies creating negative intergroup consequences. In current research, I investigated a potential cause of dehumanization: perceived cultural adoption. Moreover, drawing from value-based approach to dehumanization, I examined the role of honor related values in dehumanization of refugees. I conducted two studies. Study 1 (N = 397) showed that the perception that refugees are adopting the majority culture prompted higher honor attributions to refugees, and consequently attenuated negative attitudes, collective actions tendencies against refugees and anti-refugee policy support. This effect was only true for majority members that wished refugees to adopt majority culture. Study 2 (N = 322) replicated this effect with an experimental design and examined the mediating role of perceived identification. Overall, by employing potential cultural manifestations of dehumanization such as honor attributions, the findings displayed that perceived cultural adoption was influential in the majority's dehumanization of refugees. Theoretical and practical implications of the findings are discussed.
Keywords: Cultural appropriation.; Refugees -- Cross-cultural studies.; Interpersonal relations and culture.